Mixed-methods study on the challenges of recognising out-of-hospital cardiac arrest and dispatching ambulance services in the medical emergency coordination centre at Serdang Hospital, Malaysia - Omar, Rafiq Sumardi; Nurumal, Mohd. Said; Abu Bakar, Sherin Intan; Che Hasan, Muhammad Kamil; Jamaludin, Thandar Soe Sumaiyah; Mohd Arifin, Siti Roshaidai; Mahat, Nur Ain (Universiti Putra Malaysia Press, 2025)
Introduction: Out-of-hospital cardiac arrest (OHCA) is a major global cause of death. Early identification and telephone-guided CPR are critical for improving survival before emergency services arrive.Objectives: This study aimed to characterize emergency calls and explore the challenges faced by the Medical Emergency Coordination Centre (MECC) at Serdang Hospital, Malaysia, in recognizing OHCA cases and dispatching ambulances. Methodology: This descriptive study analyzed Malaysia Emergency Response Services (MERS) 999 calls recorded at MECC Serdang from 2018 to 2021. Data included call types, ambulance response times, six audio recordings, and in-depth interviews with eight MECC personnel. Quantitative and thematic analyses were used. Results: Of 69,194 adult-related calls in Selangor, 27% (18,554) were directed to Serdang Hospital. Life-threatening DELTA calls made up 37.5% (5,181), with 14–15% related to cardiac/respiratory arrest and 26–37% to unconsciousness. Return of spontaneous circulation (ROSC) survival for OHCA was only 0.55% in 2018 and 0% in subsequent years. Notable obstacles included “no patient found” (24 cases), prank calls (3), and duplicate events (7). Average ambulance response time was 21.42 minutes. Two main challenges emerged: (1) Effective response, hindered by language barriers, poor public awareness, lack of CPR knowledge, emotional distress, and misuse of 999 calls; (2) Effective dispatch, impacted by inexperienced staff, limited resources, and system disruptions. Conclusion: OHCA survival remains critically low due to systemic and public-related challenges. Enhanced public education and operational improvements at MECC are vital to improving emergency outcomes.